Spring Leafing Phenology Favors Younger Culms of Moso Bamboo: Aspects From Water Use Relations - Mei, Tingting; Liu, Xiang; Fang, Dongming; Zhou, Guomo; Ye, Chongyu; Li, Pingheng; Shi, Yongjun; Du, Huaqiang; Berninger, Frank; Hölscher, Dirk (Frontiers in Plant Science, 2020)
As the most widely distributed giant running bamboo species in China, Moso bamboo (Phyllostachys pubescens) can accomplish both development of newly sprouted culms and leaf renewal of odd-year-old culms within few months in spring. The two phenoloical events in spring may together change water distribution among culms in different age categories within a stand, which may differ from our conventional understanding on the negative age effect on bamboo water use. Therefore, to explore the effect of spring shooting and leaf phenology on age-specific water use of Moso bamboo and potential water redistribution, we monitored water use of four culm age categories (newly sprouted, one-, two-, and three-year-old; namely A0, A1, A2, A3) in spring from March to June 2018. For newly sprouting culms, the spring phenological period was classified into five stages (incubation, culm-elongation, branch-development, leafing, established). Over these phenological stages, age-specific accumulated sap flux density showed different patterns. The oldest culms, A3, were not influenced by leaf renewal and kept nearly constant and less water use than the other aged culms. However, A2, which did not renew their leaves, had the most water use at the two initial stages (incubation, culm-elongation) but consumed less water than A0 and A1 after the fourth stage (leafing). At the end of June, water use of the four age categaries sorted in an order of A0>A1>A2>A3, which confirms the conventional thought and observations, i.e. a negative age effect. The results indicate that new leaf flushing may benefit younger culms (A1 and A0) more than older culms (A2 and A3), i.e., increasing their transpiration response to radiation and share of the stand transpiration. With the underground connected rhizome system, the bamboo stand as an integration seems to balance its water use among culms of different ages to support the water use of freshly sprouted culms during their developing period.